Población economicamente activa ocupada y la pobreza en el Perú periodo 2016-2020 - Soria Mermao, Alexis (2023)
Treatise writers of economic theory point out that an increase in employment must bring about a reduction in poverty; hence, public policies must be aimed at promoting employment growth. The objective of this master thesis is to determine the relationship between the Economically Active Employed Population and poverty in Peru in the period 2016 - 2020. In accordance with the stated objective, the current Quantitative type research, Correlational level and of non-experimental design. The research concludes that there is an inverse statistical relationship between the Economically Active Employed Population and poverty in Peru, during the period 2016 - 2020; statement supported by the result of the Correlation Coefficient that was r = -0.883500942; and the Coefficient of Determination R2 = 0.780573914; demonstrating a very good inverse relationship and determination of the variables. The poor that make up the Economically Active Employed Population have been working mainly in the informal sector, since on average it amounts to 2,672.16 thousand people, which is equivalent to 24.24% of the workers in the informal sector. The Economically Active Employed Population had a negative behavior on average, evolving at an annual rate of -1.12%, which represents 16,303.90 thousand people per year. Poverty had a variable evolution during the 2016-2020 period.